5th AIAA Atmospheric and Space Environments Conference 2013
DOI: 10.2514/6.2013-2828
|View full text |Cite
|
Sign up to set email alerts
|

On the Feasibility of Detecting Spacecraft Charging and Arcing by Remote Sensing

Abstract: More than 50 years after the dawn of the space age, most spacecraft still do not have sensors onboard capable of detecting whether they are at potentials likely to put them at risk of severe charging and the concomitant arcing, or, indeed, even capable of detecting when or if they undergo arcing. As a result, anomaly resolution has often been hit or miss, and false diagnoses are probably common. In this paper, a few remote sensing techniques that could be applied for remotely detecting spacecraft charging and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…The principle question addressed in this paper is: Can electron-induced optical emissions resulting from interactions of space environment electron fluxes with observatory materials make significant contributions to the stray light background that could adversely affect the performance of space-based observatories? The relative importance of electron-induced light emission for spaced-based observatories is determined by comparison of the light intensity produced by relatively low-level space plasma fluxes to both external and internal sources of background light levels 1,4 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The principle question addressed in this paper is: Can electron-induced optical emissions resulting from interactions of space environment electron fluxes with observatory materials make significant contributions to the stray light background that could adversely affect the performance of space-based observatories? The relative importance of electron-induced light emission for spaced-based observatories is determined by comparison of the light intensity produced by relatively low-level space plasma fluxes to both external and internal sources of background light levels 1,4 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Earth and lunar glow backgrounds result from similar reflection of sunlight reflected from the Earth and moon scattering off of zodiacal dust. Ferguson et al discuss these background sources in near Earth orbits, and conclude that under many observation conditions the zodiacal background is the limiting external stray light component 4 . Likewise, Lightsey et al have concluded that the natural background from the zodiacal dust is the dominant external stray light source for visible and NIR background for the L2 space environment further from the Earth 2 , where contributions from the Earth and Moon shine and from bright point sources near the field of view were shown to be at least an order of magnitude less than the in-field background of the zodiacal sky 5,7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy dependence of the spectral radiance is more complicated, due to the energy-dependent penetration depth or range, ( ), in Eq. (2). For nonpenetrating radiationwhere the energy-dependent penetration depth or range, ( ), is less than the film thickness L-all incident power is absorbed in the material.…”
Section: Model Of Cathodluminescent Intensitymentioning
confidence: 99%
“…any highly disordered insulating materials used in spacecraft construction can exhibit electron-induced glow or cathodoluminescence when exposed to the space plasma environment [1]. Determinations of the absolute and relative cathodoluminescent intensity of spacecraft materials per incident electron flux are essential to predict and mitigate consequences for optical detection [2] and for stray light contamination in space-based observatories [1,3]. They also Research provide important information about the defect structure and electron transport properties of these materials [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%